Supercritical heat transfer of NOVEC 649 refrigerant in horizontal minichannels. (October 2020) - Fu, Ben-Ran; Lin, Wei-Jen
Abstract: This study investigates the influence of mass flowrates, system pressures, and channel diameters on supercritical heat transfer characteristics of NOVEC 649 refrigerant in horizontal minichannels. The experimental results demonstrate that the heat transfer coefficient significantly increases by increasing mass flux. Especially in the case of a small channel diameter, increasing mass flux can also reduce the degree of heat transfer deterioration when the fluid temperature exceeds the pseudocritical temperature. The heat transfer coefficient decreases dramatically when the fluid temperature reaches the pseudocritical temperature and then increases again when the fluid temperature exceeds and gets far from the pseudocritical temperature. Moreover, the heat transfer coefficient increases significantly with the decrease in the channel diameter. The buoyancy effect has the significant impacts on the present results, especially under experimental conditions with larger channel diameters. The heat transfer deterioration is most obvious in the results of the larger diameter. The empirical correlation of supercritical heat transfer suitable for the organic working fluid of NOVEC 649 is developed based on Jackson's correlation. Most of the errors between the values predicted by the present correlation and experimental results are within 20%, and the mean absolute error is only 11.4%.